Femoral Tunnel Enlargement After Medial Patellofemoral Ligament Reconstruction: Prevalence, Risk Factors, and Clinical Effect. (February 2014) - Berard, Jean-Baptiste; Magnussen, Robert A.; Bonjean, Grégoire; Ozcan, Soner; Lustig, Sebastien; Neyret, Philippe; Servien, Elvire
Background: In recent years, significantly more attention has been focused on the role of the medial patellofemoral ligament (MPFL) in patellar stability, and MPFL reconstruction has become a mainstay of surgical treatment of episodic patellar dislocations. Although previously described in detail after reconstruction of the anterior cruciate ligament, tunnel enlargement has not been investigated after MPFL reconstruction. Hypotheses: (1) Femoral tunnel enlargement occurs after MPFL reconstruction. (2) Patella alta, trochlear dysplasia, and tunnel malposition are risk factors for tunnel enlargement. (3) The presence of tunnel enlargement is not associated with recurrent dislocations or poorer patient-reported outcome scores after MPFL reconstruction. Study Design: Case-control study; Level of evidence, 3. Methods: Fifty-five of 59 knees treated for episodic patellar dislocations with MPFL reconstruction between 2005 and 2010 were evaluated at 1 year postoperatively for the presence of tunnel enlargement on lateral radiographs. Tunnel enlargement was defined as a tunnel area greater than 2 times that of the original tunnel. Knees with tunnel enlargement at 1 year were compared with those without tunnel enlargement. Patients were assessed for recurrent subluxations or dislocations at a mean of 3 years postoperatively, and patient-reported outcome scores were assessed in a subset of patients at a mean of 3.7 years postoperatively. Results: Tunnel enlargement was noted in 23 knees (41.8%). No differences in patient age or body mass index were noted between the 2 groups. The mean patellar height was significantly higher in the enlarged tunnel group ( P = .03). A higher prevalence of trochlear dysplasia or tunnel malposition was not demonstrated in the enlarged tunnel group. Patient-reported outcome scores and the risk of recurrent patellar instability were equal in the 2 groups. Conclusion: Femoral tunnel enlargement after MPFL reconstruction is common, with patients with patella alta at an increased risk. The influence of tunnel malposition and trochlear dysplasia on this condition requires further research. Recurrent instability and patient-reported outcome scores are not affected by tunnel enlargement.